Measurement properties of the modified and total Balance ERror SCoring System – the BESS, in a healthy adult sample. (2nd January 2018) - Kleffelgaard, Ingerid; Langhammer, Birgitta; Sandhaug, Maria; Pripp, Are Hugo; Søberg, Helene Lundgaard
Abstract: Background: Measurement properties of the modified balance error scoring system (BESS) have not been widely reported, and are variable for the BESS. Thus, the purpose of this study was to assess the inter-rater reliability and minimal detectable change (MDC), the criterion validity and floor and ceiling effects for the modified BESS and the BESS in a healthy adult sample. Methods: Two experienced raters scored the modified and total BESS on 42 healthy young adults 21 female, mean age 23.3, SD 3.8). A force plate obtained measures of body sway (sway velocity mm/s), and represented the gold standard for the criterion validity. Results: The inter-rater reliability ICC was 0.80 (95% CI 0.67–0.89) and 0.66 (95% CI 0.48–0.81) for the modified BESS and the BESS, respectively. The inter-rater MDC was 3.2 and 10.2. The calculations of the criterion validity, (Spearman's Rho) were large and medium for the modified BESS and BESS, respectively. A small ceiling effect was found for the modified BESS, but not for BESS. Conclusions: The results imply that the measurement properties for the modified BESS is acceptable, however the weaker results for the BESS may limit the utility as an outcome measure for balance for both clinicians and researchers.